Developmental expression of calretinin in the mouse cochlea - Wenjing Liu; Yongchun Zhang; Cheng Liang; Xuefang Jiang (European Journal of Histochemistry)
This study investigated the expression of calretinin (CR) in the mouse cochlea from embryonic day 17 (E17) to adulthood through immunofluorescence. At E17, CR immunoreactivity was only detected in the inner hair cells (IHCs). At E19, the IHCs and spiral ganglion neurons (SGNs) begin to express CR. At birth, CR immunoreactivity was confined primarily to the IHCs and the majority of the SGNs, as identified by TUJ1, both the cytoplasm and the nucleus of SGNs exhibited CR positivity. At postnatal day 2 (P2), auditory nerve fibers reaching the IHCs were stained for CR. CR continued to be expressed in the IHCs, whereas only single row of outer hair cells (OHCs) were positive for CR. By P5, CR expression was evident in IHCs and the three rows of OHCs, with SGNs soma and their neurite projections also displaying CR immunoreactivity. From P8 through adulthood, CR expression persisted in the SGNs and their afferent neurite projections to the IHCs, as well as in IHCs and OHCs. Dual labeling of CR with afferent nerve marker neurofilament 200 (NF200) demonstrated that NF 200-positive SGN somas were encompassed by CR-labeled plasma membrane of SGNs, and NF 200 was co-localized with CR in the afferent nerve fibers innervating the IHCs. We also described the expression of peripherin, a marker for type II SGNs, in the mouse cochlea at various postnatal stages. Peripherin showed a distinct spatio-temporal expression compared to CR in auditory nerve fibers. No co-expression of peripherin and CR was detected in adult. Dynamic expression patterns of CR in the embryonic and postnatal cochlea supported its roles in cochlear development.